Answer: 1
======================================================
Step-by-step explanation:
Check out the diagram below. Locate -2 on the horizontal x axis. Draw a vertical line through this value. Mark where the vertical line crosses the curve. Call this point P. Then draw a horizontal line through point P to have it cross the y axis. This horizontal line crosses at y = 1
In short, x = -2 leads to y = 1
So that is why f(-2) = 1
This is another way of saying f(x) = 1 when x = -2.
Note: y = f(x) since both are outputs of a function